2004
DOI: 10.1097/00004650-200401000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Nurses Enhance Performance Through Prayer

Abstract: Prayer can be empowering for performance enhancement. Researchers drew conclusions from a larger study that employed triangulation of research methods and a random sample of 1000 nurses to describe spiritual perspectives, interventions, and attitudes of nurses in the United States. This article describes the nurses' prayerful activities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 11 publications
0
2
0
1
Order By: Relevance
“…NPs need to understand adults’ perceptions of spiritual care needs (Bauer & Barron, 1995; Grant, 2004; King & Bushwick, 1994). Additionally, NPs need to be aware of their own spiritual base and comfort level in providing spiritual care (Cavendish, Luise, Konecny, & Lanza, 2004; Nagai‐Jacobson & Burkhardt, 1989; Treolar, 2000). Authentic, transpersonal, caring–healing NP–patient relationships are important in the provision of spiritual care (Cumbie, 2001; Watson, 2002, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…NPs need to understand adults’ perceptions of spiritual care needs (Bauer & Barron, 1995; Grant, 2004; King & Bushwick, 1994). Additionally, NPs need to be aware of their own spiritual base and comfort level in providing spiritual care (Cavendish, Luise, Konecny, & Lanza, 2004; Nagai‐Jacobson & Burkhardt, 1989; Treolar, 2000). Authentic, transpersonal, caring–healing NP–patient relationships are important in the provision of spiritual care (Cumbie, 2001; Watson, 2002, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…While highlighting the need for more research on this subject among nurses, Wright (2002) indicated that ignorance on the spiritual needs of nurses can also lead to burnout. Cavendish, Konecny, Luise and Lanza (2004) suggested that prayer can empower performance enhancement. Cadge and Catlin (2006) found a surprising range of religious, spiritual, existential, and other meaning-making systems that underpin how nursing staffs understand their work.…”
Section: Relevance Of Spiritualitymentioning
confidence: 99%
“…εργάτη, π. Ξάνθη 172. Πρβλ: «Γνωρίζει ο Θεός πότε πρέπει να σταματήσουν οι θλίψεις» (Χρυσόστομος 2012: 128)173 Πρόκειται ασφαλώς για μια διατύπωση επηρεασμένη από τη λόγια παράδοση.…”
unclassified